Management of Street Routing Problems Using Decision Support System - Peter Matis (Communications - Scientific letters of the University of Zilina, 2006)
Servicing a large number of customers in a city zone is often a part of many logistics chains. The capacity of one delivery vehicle is limited, and at the same time, it usually serves a large number of customers. These problems are NP hard and often called a Street Routing Problem (SRP). Problems of this category are similar to the problems named as Vehicle Routing Problem (VRP). In this paper, these problems are explored and potential solution paths for their management are described. As presented in the paper, the management of street routing problems could be effectively done only by using decision support systems or other informatics systems, such as Geographical Information Systems (GIS).